Deliberate Birth Spacing in Nineteenth Century Northern Sweden - Kolk, Martin (European Journal of Population / Revue européenne de Démographie, 2011)
International audience Fertility in nineteenth century Europe before the fertility transition has been described as high, unregulated, and stable; the extent of fertility control remains a controversial topic. The aim of this study is to determine whether there is evidence of deliberate birth spacing in northern Sweden prior to the onset of the fertility transition. This study analyses micro-level parish records of 9,636 women in nineteenth century northern Sweden--a remote but, at the time, economically dynamic frontier region of Sweden. Event history analysis reveals evidence of birth spacing that suggests some conscious birth control. Piecewise exponential models of the transition from second to third birth reveal circumstances in which parents increased or decreased the time to next birth. The results on the survival of previous children, geographic context, sex of previous children, and variations in grain prices all indicate that parents deliberately manipulated the spacing between births.